Sinergi SEO dan Hubungan Masyarakat di Era Digital: Studi Kualitatif Pada Praktik Industri E-Commerce - Grace Heidy Jane Amanda Wattimena; Akhmad Edhy Aruman; Dendy Muris (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
The digital era has significantly transformed the media and Public Relations (PR) landscape, particularly within the e-commerce sector, with Search Engine Optimization (SEO) emerging as a crucial factor in determining online visibility. This qualitative research examines the synergy between SEO and PR, focusing on how it enhances brand reach and reputation. The findings demonstrate that achieving a dominant position on the first page of search results not only influences user behavior but also plays a vital role in digital marketing strategies. Furthermore, the study highlights how SEO has evolved into a fundamental component of PR practices, enhancing organic search rankings for press releases and other communication materials. Through a comprehensive analytical approach, this research illustrates that integrating SEO into PR not only increases web traffic and revenue potential but also contributes strategically to shaping a compelling narrative for media outlets, thereby improving brand credibility. This study offers valuable insights into the evolving dynamics of the e-commerce industry, highlighting the importance of responsible and ethical strategies in fostering a sustainable relationship between PR and mass media in the digital age